Neuroprotective Effect of Moringa Oleifera Extract on Acetamiprid Induced Neurotoxicity and Apoptosis in Albino Rats - Amr A. Abdallah; Marwa A. Ibrahim; Eman A. Ibrahim; Hossam El Din H. Abdelhafez; Naglaa F. Mahmoud (Indian Journal of Forensic Medicine & Toxicology, 2021)
Acetamiprid (ACMP) can cause neurotoxicity and induces neuronal apoptosis. The ameliorative effects ofMoringa Oleifera (MO) seed extract against the neurotoxicity induced by ACMP in adult male albino ratswere investigated. Forty male albino rats were divided into 4 equal groups. The first group served as a control,the second group administered ACMP 26.8mg/kg b.w. (representing 1/10 LD50) by gavage. The third groupwas given combination of ACMP 26.8 mg/kg b.w. and MO seed extract 150 mg/kg b.w. the fourth group wasgiven MO extract only 150 mg/kg b.w. for 28 consecutive days. Results proved the efficacy of MO extractas a neuroprotective agent through the reduction of the oxidant parameter malondialdhyde (MDA) contentby 26.9%, significant increase of reduced glutathione content (GSH) by 21.4%, and elevation of catalase(CAT) and superoxide dismutase (SOD) activities by (62.2% and 40.8%) respectively, compared to ACMPintoxicated group. Consequently, gene expression analysis for Bax and NBN genes was downregulatedby 54.5% and 36.3% respectively in MO treated rats (group III) compared with ACMP intoxicated group.Moreover, restoration of the pathological tissue injuries was noticed. In conclusion, MO proved to be aneffective neuroprotective and anti-apoptotic agent against ACMP-induced toxicity.